1977
DOI: 10.1104/pp.59.5.933
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Abscisic Acid and of Hydrostatic Pressure Gradient on Water Movement through Excised Sunflower Roots

Abstract: ABSTRACIThe effect of abscisic acid on the exudation rte from decapitated roots of sunflower plants (felianthus annuus L.) was investigated in the presence and absence of an imposed hydrostatic pressure gradient. The n tude of the abscisic acid effect was constant even when suctions up to 60 cm Hg were applied to the cut stamps.When roots were bathed in a THO-labeled nutrient solution, the course of the appearance of radioactivity in the exudate, expressed as a function of exudate volume, was not affected by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
33
0

Year Published

1979
1979
2001
2001

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 9 publications
1
33
0
Order By: Relevance
“…Thirty years ago, Tal and Imber (19) and Glinka and Reinhold (33) reported that the application of ABA to the root medium of decapitated plants increases the exudation rate from the cut stump. Since that time, a number of studies have been published on this subject (16,17,20,34). Stress conditions such as flooding, chilling, and salt cause a decrease in the hydraulic conductivity of the root system that may be ameliorated by preadaptation or ABA treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty years ago, Tal and Imber (19) and Glinka and Reinhold (33) reported that the application of ABA to the root medium of decapitated plants increases the exudation rate from the cut stump. Since that time, a number of studies have been published on this subject (16,17,20,34). Stress conditions such as flooding, chilling, and salt cause a decrease in the hydraulic conductivity of the root system that may be ameliorated by preadaptation or ABA treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Promotive (2,5,6,8,14) as well as inhibitory (3, 4, 12) effects, however, have been reported with the use of ABA, depending on its concentration, the plant species, the growing conditions, and the temperature (1 1). It was recently shown that in some cases the change in volume flow (increase or decrease) results entirely from corresponding changes in the ion transport (8,13).…”
Section: Introductionmentioning
confidence: 99%
“…Reasons are given for relating the ABA effect to two separate actions, namely: (a) on water permeability, and (b) on the release of ions both from vacuoles to the cytoplasm and from symplasm to the xylem. Kinetin inhibited movement of ions to the xylem and its effect did not appear to be related to that of the ABA.ABA is known to affect both volume exudation and ion movement to the xylem in excised roots, phenomena believed to have a bearing, respectively, on water permeability and on ion transport, either from the medium to the symplasm or from the symplasm to the xylem (10).Promotive (2,5,6,8,14) as well as inhibitory (3, 4, 12) effects, however, have been reported with the use of ABA, depending on its concentration, the plant species, the growing conditions, and the temperature (1 1). It was recently shown that in some cases the change in volume flow (increase or decrease) results entirely from corresponding changes in the ion transport (8,13).…”
mentioning
confidence: 99%
“…Treatments of carrot root tissue or whole sunflower root systems with ABA have been reported to increase the hydraulic conductivity of the tissues (6,7). More recent experiments with Glycine max L. Merr.…”
mentioning
confidence: 99%